Effect of myofeedback on the threshold of the stretch reflex response of post-stroke spastic patients - Vieira, Débora; Silva, Maristella Borges; Melo, Mariana Cardoso; Soares, Alcimar Barbosa (Disability and rehabilitation, 2017)
Purpose We propose a visual myofeedback protocol as a coadjuvant therapy to standard rehabilitation of post-stroke spastic patients. We also argue in favor of the tonic stretch reflex threshold (TSRT) as a more sensitive unit for quantifying subtle changes in the spastic response that may be induced by biofeedback training. Method Sixteen volunteers with ischaemic stroke were divided into an experimental group (EG), subjected to myofeedback training in parallel with conventional physical therapy and a control group (CG), receiving only conventional physical therapy. The EG subjects underwent a six-week myofeedback training, with two sessions weekly. Both groups followed the same treatment schedule for physical therapy. The TSRTs of the volunteers' spastic muscles were assessed before the beginning of the experimental protocol and 3 weeks after it ended. Results Both groups showed some degree of improvement in the level of spasticity when the final TSRT values were compared to the initial values. However, the percentage of improvement (after-before) of the experimental group (38.59%) was significantly higher than that in the control group (18.58%). Conclusion The myofeedback training provided a significant contribution to conventional treatment, allowing for a better improvement of the spastic condition. Implications for rehabilitation Biofeedback is an effective means of improving motor control of post-stroke spastic patients. The Tonic Stretch Reflex Threshold is a more sensitive quantitative measure to assess upper-limb post-stroke spasticity. Spastic patients who participate in myofeedback training along with physical therapy can improve faster then those who participate only in traditional physical therapy rehabilitation protocols.